Theoretical Analysis of Grain Size Influence on Electrical Conductivity in Nickel and Copper - Abbas Fadhil, Sadeem; M. Jasim, Saif; Talal Suhail, Ghasaq; M Ibraheim, Sara (Al-Nahrain Journal of Science, 2025)
This work presents a new model for electrical conductivity versus grain size derived from a new theory called the time of events theory. The time of events (TE) model was applied to experimental data of electrical conductivity versus grain sizes of two metals, copper Cu and Nickel Ni due to their industrial importance in transferring electricity and electrical circuits. In addition, a comparative analysis of two other models was applied to the experimental data. The Maydas-Shatzkes model and the Andrews model. The newly derived model showed the best agreement with experimental data of Cu and Ni among all models. It uses mainly three factors: the first one is for extremely tiny grain sizes, while the second is for small grain sizes, and the third is for relatively large grain sizes. From comparing the fitting data with the Anderws models, it was noticed that the third parameter values were close to the Anderws model parameter. Therefore, Andrews' model is well applied to large grain sizes, but it deviates at extremely tiny grain sizes. This new model also predicted that the Ni data have minima and maxima, while other models did not have such a prediction.